Virome of Ixodes ricinus, Dermacentor reticulatus, and Haemaphysalis concinna Ticks from Croatia - Sameroff, Stephen; Tokarz, Rafal; Vucelja, Marko; Jain, Komal; Oleynik, Alexandra; Boljfetić, Marko; Bjedov, Linda; Yates, Rachel A.; Margaletić, Josip; Oura, Christopher A. L.; Lipkin, Walter Ian; Cvetko Krajinović, Lidija; et al. (Viruses, 2022)
Tick-borne diseases are a serious threat to both public and veterinary health. In this study, we used high-throughput sequencing to characterize the virome of three tick species implicated in the spread of vector-borne disease throughout Croatia. Ten viruses were identified, including seven potential novel species within the viral families Flaviviridae, Nyamiviridae, Rhabdoviridae, Peribunyaviridae, Phenuiviridae, and Nairoviridae.